REDESIGN OF THE WAHYU LAKE AREA, MAGETAN REGENCY - Nugroho, Hendrianto
Telaga Wahyu Tourism Area is one of the natural tourist destinations in Magetan Regency that has an interesting natural charm. As the only lake that facilitates fishing rides, Telaga Wahyu is also has beautiful lake views, surrounded by mountain views, and an area that is still dominated by vegetation. However, the development of the Telaga Wahyu Area still finds problems related to facilities, environment, design, and the existence of a master plan that is still not comprehensive. The purpose of this study is to redesign the Wahyu Lake Area to become an attractive tourist destination by considering the perceptions and preferences of prospective tourists. The design was carried out using fragmental methods and optimization design techniques. By using optimization design techniques, several criteria are obtained that are optimized, including safety, beauty, accessibility, comfortability, and security. Optimize safety by providing a Final Evacuation Site (TEA) and a Temporary Evacuation Site (TES), providing embankments and guardrails along the edge of the lake, and maintaining the presence of trees on the west side of the lake. Optimizing the beauty and attractiveness of the area by providing water tourism rides (duck boats, rowing boats), fishing, culinary tours (restaurants and food courts), photo spots, playgrounds, outbound areas and flower gardens, providing buildings that are organized following the pattern of the lake edge line, providing landmarks as an identity of the area, and providing green open space scattered around the lake, around the parking lot, around the building and along the corridors of the pedestrian path. Optimizing accessibility by providing a large off-street parking space, close to external roads, equipped with supporting facilities such as lighting and signage, and circulation in and out of the area in different parts and equipped with street furniture. Optimizing comfortability for visitors by providing pedestrian paths, disability-only lanes, and boardwalks equipped with street furniture, and providing gazebos and benchs oriented towards the lake. Optimizing safety for visitors by providing guardrails for the Telaga Wahyu Tourist Area with the surrounding area.